2010
DOI: 10.1002/ajim.20832
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial work factors and shoulder pain in hotel room cleaners

Abstract: ERI is independently associated with shoulder pain in hotel room cleaners even after adjustment for physical workload and other risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 37 publications
2
44
0
Order By: Relevance
“…The English courts have recognized that work related stressors are associated with employees' mental breakdowns and their physical health, and employers are responsible from the health of their employees (Onciul, 1996:748). Epidemiological studies show that the risks of musculoskeletal injuries or symptoms that can be increased by work stress (Bernard, 1997;Joksimovic et al, 2002;Gillen et al, 2007;Burgel et al, 2010;Eatough et al, 2012;Yu et al, 2012;in Lee, Lee, Gillen and Krause, 2014: 214). Elovainio, Kivimaki and Vahtera (2002) found that organizational justice is one of the stress factors that can cause physical and psychological reactions.…”
Section: Work Related Stressmentioning
confidence: 96%
“…The English courts have recognized that work related stressors are associated with employees' mental breakdowns and their physical health, and employers are responsible from the health of their employees (Onciul, 1996:748). Epidemiological studies show that the risks of musculoskeletal injuries or symptoms that can be increased by work stress (Bernard, 1997;Joksimovic et al, 2002;Gillen et al, 2007;Burgel et al, 2010;Eatough et al, 2012;Yu et al, 2012;in Lee, Lee, Gillen and Krause, 2014: 214). Elovainio, Kivimaki and Vahtera (2002) found that organizational justice is one of the stress factors that can cause physical and psychological reactions.…”
Section: Work Related Stressmentioning
confidence: 96%
“…Among them, two studies examined back and neck pain separately and showed that the association with effort-reward imbalance was stronger for neck pain than for back pain 17,21) . Other studies showed an association of effort-reward imbalance with shoulder pain 8) , upper extremity pain 9) , neck/upper-extremity injury 17) , low back and neck injury 21) and musculoskeletal symptoms (nonspecified) 19,23) . Our results among men are in agreement with these studies, except for upper extremity symptoms that did not display any association with effortreward imbalance in our study.…”
Section: Comparison With Literaturementioning
confidence: 98%
“…Furthermore, we also studied lower extremity symptoms, a location very seldom investigated in the topic of psychosocial work factors, and especially effort-reward imbalance 17) . We studied both biomechanical and psychosocial work exposures as risk factors of musculoskeletal symptoms, something that may be considered as a major strength; some previous studies have underlined the need to control for a potential confounding effect of biomechanical factors in the study of the association between psychosocial work factors and musculoskeletal pain 8,9) .…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations